Language Policies in Colombia: The Inherited Disdain for our Native Languages - Carmen Helena Guerrero (Asociación Colombiana de Profesores de Ingles, 2009)
As a contribution to enhance the discussion about the spread of the symbolic power of English in Colombia through a National Bilingual Policy, this paper aims at raising awareness about two main aspects: 1) Colombia has a variety of languages that should be seen as resources and not as problems (Ruíz, 1984) and 2) There is a pattern in our government language policies that tends to favor the elite. The conclusion of this paper is that not much has changed in the linguistic planning in Colombia since the Spanish colonization; privileged groups continue to legislate to favor privileged groups. This approach contributes to enlarge the gap between the haves and the haves not in Colombia.